AB0155 INTESTINAL MICROBIAL SIGNATURE IN ANKYLOSING SPONDYLITIS. (June 2019) - Cardoneanu, Anca; Burlui, Alexandra; Codreanu, Catalin; Rezus, Elena
Abstract : Background: Intestinal microbiota analysis is a current subject because of its important role in the pathogenesis of various autoimmune diseases such as intestinal inflammatory diseases or spondyloarthritis. Objectives: The objective of this paper was to perform a quantitative determination of the intestinal microbiota in patients with ankylosing spondylitis (AS) and to highlight the main characteristics of intestinal dysbiosis in these cases. Methods: We conducted a case-control prospective study that included 28 patients with AS and 32 control cases (healthy individuals). Intestinal microbiota analysis was performed by real-time PCR (polymerase chain reaction) in faeces. Intestinal microbiota analysis focused on the following bacterial species: Bacteroides, Bifidobacterium, Clostridium coccoides (XIVa) ( C. Coccoides ), Clostridium leptum (IV) (C. Leptum), Faecalibacterium prausnitzii (F. Prausnitzii), Lactobacillus, Escherichia coli (E. coli). Results: Intestinal disbiosis in AS patients was characterized by a significant bacterial decrease compared to the control arm. Some bacterial species showed a numerical growth: Bacteroides, C. coccoides and C. leptum, F. prausnitzii . In other bacterial groups there was a significant decrease: Bifidobacterium, Lactobacillus and E. coli. Statistically significant correlations were observed only for Bifidobacterium, significantly increased in the axial form of AS compared to the peripheral form (p = 0.035). Other bacterial groups were numerically elevated in the axial form of AS (except Bacteroides ), without statistically significant differences. In all AS cases, a moderate disease activity was evidenced (mean BASDAI = 4.83, mean BASFI = 9.11). BASDAI score inversely correlated with the total bacteria group (p = 0.010, r = -0.606) - intestinal dysbiosis worsens as disease activity increases. Also, direct proportional correlations were highlighted between BASDAI and F. prausnitzii (p = 0.000, r = 0.764), respectively Lactobacillus (p = 0.047, r = 0.488). An increase in AS activity is associated with an increase in proinflammatory bacteria. BASFI score statistically correlated with the total bacterial count (p = 0.000, r = -0.764), F. prausnitzii (p = 0.010, r = 0.606), Bifidobacterium (p = 0.016, r = 0.843) and E. coli (p = 0.016, r = 0.575). An important decrease in the functionality of these patients correlates with a decrease in total bacterial diversity. Improvement of intestinal dysbiosis has been observed in patients on synthetic and biological immunosuppressive therapy compared to the control arm. Conclusion: The study highlightes the characteristics of intestinal dysbiosis in AS patients. There is a direct relationship between the composition of intestinal microbiota and the AS activity scores. Specific treatment for AS leads to a decrease in proinflammatory bacteria, improving gut dysbiosis. References: [1] Mancabelli L, Milani C, Lugli GA, et al. Identification of universal gut microbial biomarkers of common human intestinal diseases by meta-analysis. FEMS Microbiol Ecol. 2017 Dec 1;93(12). [2] Breban M, Tap J, Leboime A, et al. Faecal microbiota study reveals specific dysbiosis in spondyloarthritis. Ann Rheum Dis. 2017Sep;76(9):1614-1622. [3] Breban M. Gut microbiota and inflammatory joint diseases. Joint Bone Spine. 2016Dec;83(6):645-649. [4] Gill T, Asquith M, Rosenbaum JT, Colbert RA. The intestinal microbiome in spondyloarthritis. Curr Opin Rheumatol. 2015Jul;27(4):319-325. [5] Stebbings SM, Taylor C, Tannock GW, et al. The immune response to autologous bacteroides in ankylosing spondylitis is characterized by reduced interleukin 10 production. J Rheumatol. 2009; 36:797–800. [6] Stoll ML, Kumar R, Morrow CD, et al. Altered microbiota associated with abnormal humoral immune responses to commensal organisms in enthesitis-related arthritis. Arthritis Res Ther. 2014;16(6):486. Disclosure of Interests: None declared